PEMBERDAYAAN MASYARAKAT DESA NANGA MANDAY KECAMATAN BIKA KABUPATEN KAPUAS HULU MELALUI PELATIHAN FARDHU KIFAYAH SEBAGAI UPAYA PENGUATAN LITERASI KEAGAMAAN DAN KEMANDIRIAN SOSIAL - Vera Susanti; Erikki Arifin, Abdul Rahman, Randi Hermansyah, Wardhatul Lailiah, Reni Andayani, Dea Nazila, Ningsih (Adiba Aisha Amira, 2026)
In the village of Nanga Manday, located in Bika Subdistrict, Kapuas Hulu Regency, Indonesian Borneo, community development initiatives play a crucial role in addressing local religious and social needs. The low level of religious literacy, coupled with limited access to Islamic da'wah and in-depth religious knowledge, constitutes the primary problem formulation that hinders the fulfillment of fardhu kifayah obligations among the village community. Limited access to Islamic da'wah and in depth religious knowledge in Nanga Manday Village, Bika Subdistrict, Kapuas Hulu Regency, has posed challenges in fulfilling fardhu kifayah obligations, particularly in handling deceased bodies. The community's reliance on a single community figure to perform the entire process from bathing to burying the deceased has raised concerns among residents. This community service activity aims to enhance the theoretical understanding and practical skills of Nanga Manday Village residents regarding Islamic procedures for handling the deceased. A participatory-educational approach was employed, encompassing initial observations, socialization, material delivery, and hands-on training. The activity demonstrated high community enthusiasm, along with significant improvements in knowledge and skills across all stages of handling the deceased, from bathing, shrouding, praying over, to burying. Ultimately, the training successfully empowered the community to independently and correctly fulfill fardhu kifayah obligations, thereby reducing dependency and enhancing religious social responsibility within the community. This success not only opens opportunities for sustainable collaboration with local religious institutions such as Majelis Ta'lim, but also serves as a replicable model of community service for other remote villages in West Kalimantan, aimed at sustaining long-term independence, strengthening sharia-based social networks, and supporting sustainable community development in line with the national village development vision.